2016
DOI: 10.1021/jacs.6b07026
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Chemoselectivity of Metal N-Aryl Nitrene Reactivity: C–H Bond Amination versus Electrocyclization

Abstract: A mechanism study to identify the elements that control the chemoselectivity of metal-catalyzed N-atom transfer reactions of styryl azides is presented. Our studies show that the proclivity of the metal N-aryl nitrene to participate in sp-C-H bond amination or electrocyclization reactions can be controlled by either the substrate or the catalyst. Electrocyclization is favored for mono-β-substituted and sterically noncongested styryl azides, whereas sp-C-H bond amination through an H-atom abstraction-radical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 169 publications
1
28
0
Order By: Relevance
“…Driver found that the [Fe(OEP)Cl]-catalyzed reactions of styryl azides having tertiary allylic C-H bonds show selectivity toward allylic C-H bond amination (Scheme 8). [61] The lowered ratio of 2H-indole/indole (2 : 1) formed in a deuterium-labeling experiment is consistent with the proposal that the two products are formed from the different reaction routes of C-H amination and electrocyclization, respectively. For styryl azides that do not contain tertiary C(sp 3 )-H bond, their [Fe(OEP)Cl]-catalyzed reactions could also produce formal C-H amination products that have the newly formed C-N bond on the original β-carbon position of the styryl azides (Scheme 8).…”
Section: Recent Advancessupporting
confidence: 84%
See 1 more Smart Citation
“…Driver found that the [Fe(OEP)Cl]-catalyzed reactions of styryl azides having tertiary allylic C-H bonds show selectivity toward allylic C-H bond amination (Scheme 8). [61] The lowered ratio of 2H-indole/indole (2 : 1) formed in a deuterium-labeling experiment is consistent with the proposal that the two products are formed from the different reaction routes of C-H amination and electrocyclization, respectively. For styryl azides that do not contain tertiary C(sp 3 )-H bond, their [Fe(OEP)Cl]-catalyzed reactions could also produce formal C-H amination products that have the newly formed C-N bond on the original β-carbon position of the styryl azides (Scheme 8).…”
Section: Recent Advancessupporting
confidence: 84%
“…Another interesting study of heme-type iron catalyzed-C-H bond amination reaction is Driver's exploration on *Fe(OEP)Cl+catalyzed conversion of styryl azides. [61] Transition-metal-catalyzed intramolecular N-group transfer reactions of styryl azides might give allylic C-H bond amination or electrocyclization products (Scheme 8). Driver found that the [Fe(OEP)Cl]-catalyzed reactions of styryl azides having tertiary allylic C-H bonds show selectivity toward allylic C-H bond amination (Scheme 8).…”
Section: Recent Advancesmentioning
confidence: 99%
“…Scheme 1 shows the synthetic route to designed compound 2. 1-Boc-4-piperidone (5) was condensed with dimethyl carbonate to give 6 16 and then reacted with methyl vinyl ketone to synthesize 7. 17 Robinson annulation of 7 was carried out in the presence of pyrrolidine and acetic acid, 17 following which demethoxycarbonylation was performed via hydrolysis of the resulting ester 8 with a 1 M aqueous NaOH solution to obtain 9.…”
Section: Resultsmentioning
confidence: 99%
“…While [Ir(cod)(OMe)] 2 selectively promoted electrocyclization, an iron porphyrin catalyst favored C−H amination ( Scheme 12). [54] …”
Section: Intramolecular Nitrene Transfersmentioning
confidence: 99%